2019
DOI: 10.1002/pat.4697
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nucleating agent supported on zeolite via the impregnation on the crystallization ability of isotactic polypropylene and its mechanism

Abstract: Addition of an α‐nucleating agent is the simple and effective method to increase nucleation efficiency of isotactic polypropylene (iPP). However, severe agglomeration and poor dispersibility of sodium 2,2′‐methylene‐bis(4,6‐di‐tertbutylphenyl) phosphate (NA11) decrease the nucleation efficiency in the iPP, and much more nucleating agent is needed to maintain the nucleating property. As a result, it becomes the key how to decrease the size of NA11 and increase the nucleating property. In this paper, zeolite 4A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In 2021, Xin et al. reported a synthesis of 2,2’‐methylene‐bis(4,6‐di‐ tert ‐butylphenol) phosphate ( 17 a ) that is useful as a plastic nucleating agent and a fine chemical [27] . Phosphate 17 a was synthesized from POCl 3 and 2,2’‐methylene‐bis(4,6‐di‐ tert ‐butyl) phenol ( 16 a ).…”
Section: Continuous‐flow Synthesis Using Pcl3 and Pocl3mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Xin et al. reported a synthesis of 2,2’‐methylene‐bis(4,6‐di‐ tert ‐butylphenol) phosphate ( 17 a ) that is useful as a plastic nucleating agent and a fine chemical [27] . Phosphate 17 a was synthesized from POCl 3 and 2,2’‐methylene‐bis(4,6‐di‐ tert ‐butyl) phenol ( 16 a ).…”
Section: Continuous‐flow Synthesis Using Pcl3 and Pocl3mentioning
confidence: 99%
“…In 2021, Xin et al reported a synthesis of 2,2'-methylenebis(4,6-di-tert-butylphenol) phosphate (17 a) that is useful as a plastic nucleating agent and a fine chemical. [27] Phosphate 17 a was synthesized from POCl 3 and 2,2'-methylene-bis(4,6-di-tertbutyl) phenol (16 a). In this reaction, the in situ generated hydrogen chloride was trapped by Et 3 N. In order to avoid an undesired clogging of the flow reactor by precipitations of the amine hydrochloride salts, solvents were preliminarily screened using a batch reactor.…”
Section: Nucleophilic Substitutions Of Pcl 3 and Pocl 3 With Alcohol ...mentioning
confidence: 99%
“…2,2′-Methylene-bis­(4,6-di- tert -butylphenol) phosphate chloride is the intermediate of many plastics nucleating agents such as NA-40, NA-45, and NA-71, which are considered as extremely important chemicals in the fine chemical industry and have a broad application in the modified polypropylene. Generally, 2,2′-methylene-bis­(4,6-di- tert -butylphenol) phosphate chloride ( 2 ) can be synthesized by a highly exothermic homogeneous condensation reaction between 2,2′-methylene-bis­(4,6-di- tert -butyl) phenol ( 1 ) and POCl 3 with triethylamine as the acid-binding agent base, along with the formation of triethylamine hydrochloride ( 3 ) (Scheme ). An obvious thermal effect appeared upon the contact of all the reactants, so potential danger must be taken into account especially when the heat transfer capacity of the reactor is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Kimura et al [13] proposed, for the first time, that the synergistic effect o APAl-OH and lithium laurate can reduce the haze of PP from 32% to 5%. As a kind o additive nucleating agent, NA-21 is difficult to disperse in the iPP system because of the presence of strong polar phosphate compounds in its components [14]. At present, many studies have been devoted to improving the dispersion of the APs nucleating agents in the iPP matrix [15][16][17].…”
Section: Introductionmentioning
confidence: 99%